2013
DOI: 10.1007/s13277-013-0725-z
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-mediated Stat3 activation is essential for CXCL12-induced cell invasion in bladder cancer

Abstract: CXCL12/CXCR4 signaling plays important roles in tumor cell metastasis in many types of cancers, and CXCR4 is the key regulator of cell motility in bladder cancer. Emerging evidence suggests that transcription-3 (Stat3) activation is associated with bladder cancer cell growth and survival, while the relationship between CXCL12/CXCR4 signal and Stat3 activation remains unclear. In this study, expression analysis of bladder cancer and adjacent normal tissues showed that higher CXCR4 expression was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Moreover, STAT3 activation is involved in chemoresistance in human NSCLC 30. STAT3 is a major downstream target of JAK2 involved in CXCL12-induced proliferation of SCLC and bladder cancer cells 31,32. In our study, treatment with the JAK2 antagonist AG490 completely reversed the anti-apoptotic effect of CXCL12 in A549 cells ( P <0.05).…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, STAT3 activation is involved in chemoresistance in human NSCLC 30. STAT3 is a major downstream target of JAK2 involved in CXCL12-induced proliferation of SCLC and bladder cancer cells 31,32. In our study, treatment with the JAK2 antagonist AG490 completely reversed the anti-apoptotic effect of CXCL12 in A549 cells ( P <0.05).…”
Section: Discussionsupporting
confidence: 51%
“…Aberrant STAT3 signaling promotes initiation and progression of human cancers by either inhibiting apoptosis or inducing cell proliferation, angiogenesis, invasion, and metastasis. It has been reported that CXCR4 signaling activates the JAK2/STAT3 pathway in many types of cancers (36,37). To elucidate the signaling pathways underlying sinomenine-mediated responses in osteosarcoma cells, we further investigated the effects of sinomenine on CXCR4 and STAT3 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study demonstrated that higher CXCR4 expression was associated with Stat3 signaling activation in bladder cancer [30]. CXCR4 knockdown in bladder cancer T24 cells impaired CXCL12-induced cell invasion and Stat3 activation (Shen et al, 2013). Therefore, it will be interesting to investigate the regulatory mechanisms of SRC-3 on CXCR4 expression in the future.…”
Section: Discussionmentioning
confidence: 99%